2017
DOI: 10.1515/tnsci-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities are not a predictors of SSTR4met in alcoholics

Abstract: BackgroundGenome methylation may modulate synaptic plasticity, being a potential background for mental disorder. Adverse childhood experiences (ACEs), known to be frequently reported by patients with alcohol dependence (AD), have been proposed as one of environmental inequities influencing DNA methylation. The study is aiming 1.To assess a promoter region methylation in gene for somatostatin receptor subtype-4 (SSTR4), a receptor for somatostatin, a neurotransmitter engaged in neuroplasticity and memory format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Moreover, a case–control study on 176 Polish individuals with ethanol dependence and 127 healthy volunteers found that the former group reported significantly higher numbers of childhood adversities. However, childhood trauma was not found to be a predictor of SSTR4 methylation, despite 21.6% of this population displaying increased SSTR4 promoter methylation compared with 2.3% of controls [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a case–control study on 176 Polish individuals with ethanol dependence and 127 healthy volunteers found that the former group reported significantly higher numbers of childhood adversities. However, childhood trauma was not found to be a predictor of SSTR4 methylation, despite 21.6% of this population displaying increased SSTR4 promoter methylation compared with 2.3% of controls [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACEs and homozygosity for the major T allele of SSTR4 rs2567608 significantly raise the risk for lifetime suicide attempts in AD patients (i.e., homozygosity remained a significant predictor only in male AD patients) [ 11 ]. One study reported that the promoter region of SSTR4 , which encodes the somatostatin receptor subtype 4, was more frequently methylated in AD patients than in controls; however, SSTR4 promoter region methylation was not associated with the sum of ACEs categories or with any other factor analyzed in that study (term and course of labor, age and sex, nutritional habits, alcohol drinking severity, cigarette smoking) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…AD patients were invited to participate in the study at least 1 week from the beginning of hospitalization to exclude patients with acute withdrawal syndrome at the time of the study. Of the 209 patients who gave informed consent to participate in the study, 33 did not undergo further analysis because of the following exclusion criteria (of note, some individuals fit multiple exclusion criteria): (1) co-occurring psychiatric disorder requiring current medication ( n = 6); (2) returning an uncompleted study questionnaire ( n = 30); (3) consent withdrawal, primarily due to finding the questions too intimate or time-consuming ( n = 3); (5) prior receipt of chemotherapy consisting of drugs that influence DNA methylation, i.e., 5-azacytidin and decitabine (criterion implemented for the purpose of the previous study on genome methylation ( n = 1) [ 20 ]; and (6) insufficient quality of DNA available ( n = 18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations